Webinar Summary Report: Targeting Tools 2.0: Targeting and out-scaling interventions in agricultural systems - Mutua, John Y. (2021)
The first webinar to raise awareness on Targeting Tools 2.0 was held on the 24th November 2020 through GoToWebinar. Project team members from two ongoing projects participated: BMZ: Improved forage grasses: Making the case for their integration into humid- to sub-humid livestock production systems in Kenya and Ethiopia and IFAD: Climate-smart Dairy Systems in East Africa through Improved Forage and Feeding Strategies. Scientists from the Alliance of Bioversity International and CIAT guided participants through the tool’s capabilities and how to leverage the features to assess gaps and opportunities for improving and expanding the choice of intervention options while designing programmes for sustainable agricultural intensification at a range of scales. 32 participants from drawn from academia, NGO and research institutions participated in the discussions following the presentations.